Cutaneous Plasmacytosis: A Pitfall For B and Plasma Cell Neoplasms. (28th October 2020) - Giraldo, C N; Myers, D; Holmes, A; Dodd, J; Wendi, W
Abstract: Introduction/Objective: Cutaneous plasmacytosis (CP) is an uncommon condition typically affecting Asian males in the 3rd to 5th decades. It is thought to be a reactive process that classically presents with asymptomatic, red-brown, plaques and nodules on the face and neck. It has been associated with polyclonal hypergammaglobulinemia and systemic involvement. Histologically it is characterized by dense superficial and deep dermal infiltrates of mature plasma cells with polyclonal differentiation on in-situ hybridization (ISH). The differential diagnosis includes neoplastic plasma cell processes, characteristically with monoclonal plasma cell infiltrate, and mature B cell neoplasms with polyclonal plasma cell differentiation. Methods: We report a case of a 69 year old Caucasian male who presented with asymptomatic, enlarging red-brown nodules on bilateral nasal ala. Histologic examination revealed dense, superficial plasma cell infiltrate, concerning for a plasma cell neoplasm. CD138 and Kappa/Lambda ISH demonstrated plasma cell polyclonality. Further workup ruled out infectious or systemic involvement and a plasma cell dyscrasia was ruled out by Hematology/Oncology. Results: These findings supported the diagnosis of CP. Treatment with intralesional steroids showed initial improvement with regrowth of the nodules. To date, treatment with topical steroids and CO2 laser ablation are being considered. Conclusion: CP is reported as type of pseudolymphoma, which is described as a reactive lymphoproliferation that histopathologically and/or clinically imitates cutaneous lymphoma. The pathogenesis is unknown, however, there are studies suggesting an association with increased interleukin-6, which is involved in the differentiation of B cells to mature plasma cells. The majority of patients with CP have a favorable prognosis. There has been variable success with both topical and intralesional treatment to include, cyclophosphamide, topical tacrolimus, prednisone, intralesional steroid therapy, topical psoralens combined with ultraviolet A exposure, and other chemotherapies. Familiarity with this rare entity is imperative to prevent misdiagnosis and overtreatment.